Same-day discharge for atrial fibrillation ablation: outcomes and impact of ablation modality. Issue 2 (27th September 2022) - Deyell, Marc W; Hoskin, Kurt; Forman, Jacqueline; Laksman, Zachary W; Hawkins, Nathaniel M; Bennett, Matthew T; Yeung-Lai-Wah, John A; Chakrabarti, Santabhanu; Krahn, Andrew D; Andrade, Jason G
Abstract: Aims: Same-day discharge is increasingly common after catheter ablation for atrial fibrillation (AF). However, the impact of same-day discharge on healthcare utilization after ablation and whether this differs by ablation modality remains uncertain. We examined the safety, efficacy, and subsequent healthcare utilization of a same-day discharge protocol for AF ablation, including radiofrequency (RF) and cryoballoon ablation, in a contemporary cohort. Methods and results: All consecutive patients for whom full healthcare utilization data were available at two centres and who underwent AF ablation from 2018 to 2019 were included. Same-day discharge was the default strategy for all patients. The efficacy and safety outcomes were proportions of same-day discharge and readmission/emergency room (ER) visits, and post-discharge complications, respectively. Of the 421 patients who underwent AF ablation (mean 63.3 ± 10.2 years, 33% female), 90.5% (381/421) achieved same-day discharge with no difference between RF and cryoballoon ablation (89.8 vs. 95.1%, adjusted P = 0.327). Readmission ≤30 days occurred in 4.8%, with ER visits ≤30 days seen in 26.1% with no difference between ablation modalities ( P = 0.634). Patients admitted overnight were more likely to present to the ER (40.0 vs. 24.7% with same-day discharge, P = 0.036). The overall post-discharge complication rate was low at 4/421 (1.0%), with no difference between ablation modality ( P = 0.324) and admission/same-day discharge ( P = 0.485). Conclusion: Same-day discharge can be achieved in a majority of patients undergoing RF or cryoballoon ablation for AF. Healthcare utilization, particularly ER visits, remains high after AF ablation, regardless of ablation modality or same-day discharge. Graphical Abstract: Graphical Abstract